Les alternances codiques et le rôle de l’anglais chez les étudiants en mobilité à l’ère de la mondialisation - Valentina Candidi (Recherches en didactique des langues et des cultures)
In today's world, the English language has assumed a pivotal role in business transactions and international relations. The process of globalization has facilitated the internationalization of higher education, resulting in a steady increase in student mobility. This research examines the prevalence of English in the code-switching practices of a heteroglot group of students in France. We present several examples from our data to illustrate the dynamic exchange that characterizes the language repertoires of these learners in various multilingual interaction scenarios. Using the action research method, this paper offers an overview of the students' multilingual backgrounds, with particular emphasis on the role of English in facilitating effective communication and the attainment of their communicative goals.